Physics of knuckleballs - Darbois Texier, B.; Cohen, C.; Quere, D.; Clanet, C. (New Journal of Physics, 2016)
Zigzag paths in sports ball trajectories are exceptional events. They have been reported in baseball (from where the word knuckleball comes from), in volleyball and in soccer. Such trajectories are associated with intermittent breaking of the lateral symmetry in the surrounding flow. The different scenarios proposed in the literature (such as the effect of seams in baseball) are first discussed and compared to existing data.Wethen perform experiments on zigzag trajectories and propose a new explanation based on unsteady lift forces. In a second step, we exploit wind tunnel measurements of these unsteady lift forces to solve the equations of motion for various sports and deduce the characteristics of the zigzags, pointing out the role of the drag crisis. Finally, the conditions for the observation of such trajectories in sports are discussed.